Health Problems experienced by Peri-menopausal Women and their Perception towards Menopause - Chalise, Gita Dhakal; Shrestha, Sarala; Thapa, Sumana; Bharati, Mamata; Pradhan, Subhadra; Adhikari, Bibhav (Journal of Nepal Health Research Council, 2022)
Background: Perimenopause is a period of physiologic changes in the women's lives when they approach reproductive senescence along with temporal changes in health and quality of life. During this period, many women present with problems of hot flushes; altered mood and sleep; and vaginal and sexual changes. The objective of this study was to identify the health problems experienced and perception towards menopause among perimenopausal women of Kathmandu.Methods: This descriptive cross-sectional study was carried out among purposively selected 180 women from two wards of Nagarjun Municipality, Kathmandu, who were aged 45 to 55 years. By using a semi-structured interview schedule, face to face interview was taken at the respondents' residence. The collected data were analyzed using descriptive and inferential statistical techniques.Results: The mean age of the respondents was 48.98±3.908 years and their mean body mass index was 27.42±3.645 kg/ m2. About 35.0 % of the respondents had experienced cessation of menstruation and their mean age at menopause was 47.84±4.41years. The common physical problems reported by them were joint and muscle pain (17.2%), hot flushes (14.4%) and night sweats (13.3%). Vaginal itching (16.7%), loss of libido (10.6%) and dry vagina (5%) were commonly reported sexual problems. Anxiety (16.7%), poor memory (8.9%), and irritability (7.2%) were the psychological problems reported by them. Most (77.8%) of them had a positive perception and the rest (22.2%) had a negative perception towards menopause. Their perception status was significantly associated with their age and family type. Conclusions: Perimenopausal women experience several physical, sexual and psychological problems during the menopause transition. Keywords: Health problems; perception towards menopause; perimenopause.